Psychometric Evaluation and Establishing Norms of Croatian SF-36 Health Survey: Framework for Subjective Health Research - Maslić Seršić, Darja (Croatian Medical Schools, 2006)
AIM: To provide population norms and evaluate metric characteristics of the Croatian version of SF-36 Health Survey, an internationally used instrument for assessing subjective health. METHOD: The questionnaire was administered to a representative sample of Croatian adult population (n = 9070). Three standard techniques were used in data analysis: reliability tests, descriptive statistics, and factor analysis. The population norms were presented in two standard forms – the SF-36 Health Profile and percentile values for different age groups of men and women. RESULTS: The Croatian version of the SF-36 had generally acceptable metric characteristics including its construct validity. The internal consistency of the SF-36 scales ranged from 0.78 to 0.94. Pearson bivariate correlations showed moderate associations between SF-36 scales, and factor analysis provided one latent dimension underlying all SF-36 scales which explained 63.3% of the score variance. Less favorable results were obtained concerning its discriminative validity. All SF-36 scales showed negative asymmetry of score distributions, and some had high floor and ceiling effects – skewness estimations ranged from -0.12 to -0.91, with the highest floor effect of 30% and ceiling effect of 63%. CONCLUSION: Presented population norms for the Croatian version of SF-36 Health Survey showed that SF-36 may be used as a valid and reliable instrument in research in subjective health of Croatian population.